(3GdJcedI dcJGH GdUdIs - (3CHh YHO Gddg eMeO Hf YHO Gddg Hf CHi HcQ GdbVGYi GdHdfSi , GHf GdCHGQs; (3GHf HTchGd , Nda Hf YHO Gdedc Hf eSYhO Hf HTchGd GdNRQLj GdCfUGQj, CHhGdbGSe,J (B578 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI (B( (3eMeO Hf eMeO Hf Ydi GdYci (B) (3ef Cgd TGWHI jcfi CHG YeQ hjYQa HGHf s
(3BNQgG (B:s
(3jfJgi HJQLeI (B( (3YHO GdhgGH Hf YHO Gddg Hf YHO GdhgGH (B) (3ef Cgd eUQ hScf HZOGO hjYQa HGdWfObGFi fSHg Edi bQjI HeUQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B286s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs